Association between glycated hemoglobin and biomechanical properties of the skin with type 2 diabetes by using an electro-mechanical skin device - Chen, Fei; Zhou, Jiahui; Chen, Xianxian; Deng, Xuchen; Zhou, Jiangfeng; Pan, Xin; Chen, Zimiao; Gong, Xiaohua (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to evaluate the association between glycated hemoglobin (HbA1c) levels and biomechanical properties of the human skin with type 2 diabetes mellitus (T2DM) patients using an electro-mechanical skin device.MethodsA cross-sectional study enrolled 136 T2DM patients and 190 healthy controls. Biomechanical properties of the skin were measured with an electro-mechanical skin device(Khelometer®)at different skin sites (forearm, pretibial, and instep regions). The parameters, including F (Maximum rebound force), M (retention rate of rebound force), R (rise response rate) and H (rebound force hysteresis) by Khelometer®, represent biomechanical properties of the human skin.ResultsT2DM patients showed significantly higher F values and lower M, R, and H values compared to healthy controls. HbA1c levels were positively associated with F values and negatively associated with M, R, and H values across different skin sites. Participants with higher F values had significantly higher HbA1c levels. Restricted cubic spline analysis revealed strong nonlinear associations between HbA1c and skin biomechanical properties.ConclusionsThe data indicate the electro-mechanical skin device is useful to quantitate the biomechanical properties of the skin. Furthermore, this study demonstrates a nonlinear relationship between HbA1c levels and the biomechanical properties of the skin. These findings add to the evidence to support the impact of elevated HbA1c on biomechanical properties in individuals with T2DM.